Insight: um estudo experimental com ratos - Leonardi, Jan Luiz (2012)
Insight has been interpreted in behavior analysis as the sudden resolution of a problem when two or more different repertoires, previously learned separately, interconnect in a new situation without direct training, producing original sequences of behavior. A small body of research has shown some variables which appear to contribute to the production of this phenomenon, but methodological problems, in particular the use of arbitrary objects in the problem-situation and the delay between response and reinforcer, limit its relevance. Under the light of these considerations, the objective of this research was to investigate the phenomenon of spontaneous interconnection of repertoires (or insight ) with variations in the procedures employed in the area. These were: (a) the object that should be reached by the subjects in the problem-situation was established as a reinforcing stimulus before the phases of testing and training; (b) the delay between the target response (from training and testing) and consumption of the primary reinforcer (water) was reduced by the construction of a drinking magazine that could be moved toward the subject. Two Wistar rats were used as experimental subjects. The equipment and materials were a circular chamber of 69 cm in diameter and 50 cm high, four acrylic cubes coated with black cardboard, a nylon string that drove the movement of the cube along the camera, and a buzzer. The procedure was divided in six phases: (a) training to the drinking magazine, (b) pre-test of insight, (c) training to push the cube, (d) intermediate test of insight, (e) training to climb on the cube and rise, (f) final test of insight. In the test of insight situation, the subject should reach the drinking magazine positioned at the top of the chamber by pushing an acrylic cube in its direction and climbing on the cube to drink. Water were used as reinforcement in a continuous schedule of reinforcement. The results showed that none of the subjects solved the problem in a sudden, direct and continuous way, criteria used to qualify the performance as insight . Nevertheless, the procedure used in this experiment has heuristic value as it represents an attempt to produce the phenomenon without the use of arbitrary objects (which significantly reduces the number of training sessions), and rendered the concept of functional generalization unnecessary. Finally, this research points out obstacles that the area faces in the study of insight , such as the difficulty in replicating Epstein s research and the problems generated by the use of arbitrary objects in the problem-situation, not to mention the limitations imposed by the behavioral interpretation of the phenomenon